ROLE OF PEDAGOGY COMPETENCE OF A CONTROLLER-TRAINER IN SIMU-TRAINING OF AIR TRAFFIC CONTROLLERS - Петращук, О.; Немлій, Л. (Proceedings of National Aviation University (archive), 2012)
The article focuses on the issue of pedagogy competence of an ATCO-trainer as a constituent of hisoverall professional competency/capacity to provide quality SIMU- training of the air traffic controllers. Thecurrent University curriculum for abinitio controllers does not provide developing of the pedagogicalcompetence. But it is requested very much when an air traffic controller is employed as a controller-trainerfor SIMU-training. It is suggested to include pedagogical science as a course in the University programme